Aplicação da Aprendizagem Baseada em Problemas (ABP) no ensino na saúde em um Programa de Residência Multiprofissional. - Leite Silva, Isis Mariane (Saberes Plurais)
: Problem-Based Learning (PBL) stands out as an active learning methodology that uses problem solving as a guide for discussions and conclusions. Objective: To describe an educational intervention for the preceptorship of Nutrition in Oncology through PBL, associated with prior pedagogical planning. Experience report: The experience reports the use of ABP in health teaching for Nutrition residents, of a Multiprofessional Residency (MR) in Oncology. Initially, the preceptor prepared a clinical case, so that the problem was exposed and residents could recover their previous knowledge. In the second moment, the residents researched the scientific literature on solving the problems and, finally, in a discussion guided by the preceptor, they presented the findings to resolve the questions. The importance of prior planning to achieve the intended objectives was observed. The experience brought benefits such as the hitherto unrealized use of active learning methodologies in the Residence, the adherence of residents to this form of teaching-learning observed through the search for theoretical references and the participatory discussion carried out, the diversity in knowledge sought and addressed, the relationship of trust and the development of speaking and writing skills of preceptors and residents, in addition to instigating permanent professional improvement. As challenges, residents’ lack of knowledge about PBL, lack of understanding of learning objectives and activity evaluation methodologies were observed. Conclusion: The health teaching experience reported showed the importance of planning in the development of PBL in resident training. There is a need for the topic to be included in the preceptor’s ongoing education process and to expand the experience for preceptors and residents of other professions that make up MR.